Elemental characterization of wild edible plants from countryside and urban areas. (15th June 2015) - Renna, Massimiliano; Cocozza, Claudio; Gonnella, Maria; Abdelrahman, Hamada; Santamaria, Pietro
Highlights: Wild edible plants were collected from countryside and urban areas. The content of thirteen elements was determined by ICP-OES. Wild edible plants may give a contribution to the elements intake for consumers. In a few case wild edible plants may supply high level of potentially toxic elements. Abstract: Thirteen elements (Na, K, Ca, Mg, Fe, Mn, Cu, Zn, Cr, Co, Cd, Ni and Pb) in 11 different wild edible plants (WEP) ( Amaranthus retroflexus, Foeniculum vulgare, Cichorium intybus, Glebionis coronaria, Sonchus spp., Borago officinalis, Diplotaxis tenuifolia, Sinapis arvensis, Papaver rhoeas, Plantago lagopus and Portulaca oleracea ) collected from countryside and urban areas of Bari (Italy) were determined. B . officinalis and P . rhoeas could represent good nutritional sources of Mn and Fe, respectively, as well as A . retroflexus and S . arvensis for Ca. High intake of Pb and Cd could come from P . lagopus and A . retroflexus (1.40 and 0.13 mg kg −1 FW, respectively). WEP may give a substantial contribution to the elements intake for consumers, but in some cases they may supply high level of elements potentially toxic for human health. Anyway, both ANOVA and PCA analyses have highlighted the low influence of the harvesting site on the elements content.